Analysis of the technical condition of the inner facades of the Donjon at the Klodzko Fortress - Drobek, Katarzyna; Trochonowicz, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The article presents an analysis of the technical condition of the interior facades of the Donjon in the Klodzko Fortress. The aim of the study is to understand the processes leading to the deterioration of the architectural heritage. The Klodzko Fortress, located in Lower Silesia, is one of the most important and largest fortifications in Poland, with a rich history dating back to the Middle Ages. Modern structures date mainly from the 17th and 18th centuries. The article focuses on the analysis of the technical condition of the internal facades of the donjon, which are exposed to various degradation factors such as weather conditions, human activity and time. The studies were carried out in 2016 and 2023. They aimed to determine the current condition of the donjon's internal facades and the causes of the observed deterioration. The two surveys made it possible to assess differences in damage and the speed of degradation processes and their impact on the current state of the facades.